PENINGKATAN PRODUKTIVITAS KARYAWAN MELALUI MANAJEMEN SDM ISLAMI DAN KOMITMEN AFEKTIF - Kris Dianingsih; Ardhian Adhitama (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
This research was conducted to identify how values and the nature of influence are exerted between independent research variables which include Islamic HR management on business sustainability, Islamic HR management on affective commitment and the effect of affective commitment on business sustainability. The population in this study are all employees at PT. RotiQu with a total of 70 respondents. However, the number of respondents who filled out the questionnaire properly was 68 questionnaires so that the sample quantity studied was 68 respondents. The data analysis method used is a quantitative method using multiple linear regression analysis. The sample in this study were some employees of PT. RotiQu with purposive sampling method. The research analysis method used is multiple linear regression analysis with SPSS version 18. The results of the research analysis show that Islamic HR management has a positive and significant effect on employee productivity. Islamic HR management has a positive and significant effect on affective commitment. Affective commitment has a positive and significant effect on employee productivity and affective commitment is able to mediate the indirect effect of Islamic HR management on employee productivity. Keywords: Marketing Creativity, Product Innovation, Competitive Advantage, Business Performance